Analisis Demokrasi pada Pengisian Jabatan Gubernur dan Wakil Gubernur di Daerah Istimewa Yogyakarta - Putra, Akbar Ardya; Candrakirana, Rosita; Puri Maharani, Andina Elok (Jurnal Hukum & Pembangunan, 2025)
The aim of this research is to analyze the implementation of democracy in the process of filling the governor and deputy governor positions in the Yogyakarta Special Region. This is regulated in the Special Areas Act No. 13/2012. The Act stipulates that the candidates for governor can only be the descendants of the Yogyakarta Sultanate and the candidates for deputy governor can be the descendants of the Duchy of Pakualaman. Following these provisions, there are differences between the special region of Yogyakarta and other regions using general elections to fill regional heads. The results of the study show that the nomination of Governors and Deputy Governors in the special region of Yogyakarta does not violate the principles of democracy already present in Indonesia, because the Constitution directly regulates this issue, but does not use general elections in the process. The study also showed that the 1945 Constitution also strengthened the establishment of the post of Governor and Deputy Governor in Yogyakarta's special region, as Indonesia's independence was a strong historical background.